Persepsi dan Praktik Masyarakat terhadap Zihar dalam Perspektif Fiqh Munakahat: Studi Kasus di Desa Simangambat, Kecamatan Dolok Sigompulon, Kabupaten Padang Lawas Utara - Isman Nuddin Ritonga; Heri Firmansyah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to analyze public perceptions of zihar, examine its practice in domestic life, and explain its legal and social implications from the perspective of fiqh munakahat. The study employed a qualitative approach with field research conducted in Simangambat Village, North Padang Lawas Regency. Data were obtained through in-depth interviews with religious leaders, community leaders, village officials, and married couples. Data were analyzed thematically by comparing social practices and normative provisions of Islamic law. The results reveal a clear gap between the norms of fiqh munakahat and social reality, where zihar is perceived as an emotional expression or a joke without legal consequences. This finding indicates a weak internalization of Islamic family law and the potential for injustice in marital relations. This study emphasizes the importance of strengthening contextual and sustainable fiqh munakahat education at the community level.